Princeton problems in physics with solutions - Newbury, Nathan; Newman, Michael; Ruhl, John; Staggs, Suzanne; Thorsett, Stephen (Hyderabad, University Press, 1991)
Aimed at helping the physics student to develop a solid grasp of basic graduate-level material, this book presents worked solutions to a wide range of informative problems. These problems have been culled from the preliminary and general examinations created by the physics department at Princeton University for its graduate program. The authors, all students who have Successfully completed the examinations, selected these problems on the basis of usefulness, interest and originality and have provided highly detailed solutions to each one. The first four chapters pose problems in the areas of mechanics, electricity and magnetism, quantum mechanics and thermodynamics and statistical mechanics, thereby serving as a review of material typically covered in undergraduate courses. Later chapters deal with material new to most first-year graduate students, challenging them on such topics as condensed matter, relativity and astrophysics, nuclear physics, elementary particles and atomic and general physics.
Bibliographical references 311-312p; Index 313-319p
Keywords: Physics- Problems and solutions; Physics